Operational staretgy to manage mature oil and gas fields in maninjau production sharing contract with new fiscal regime - Kartadinata, Rian; Nizar, Adirizal (The Indonesian Journal of Business Administration, 2018)
Abstract: Indonesian manufacturing industry has developing significantly. The increase in consumption is one of the factors that contribute to this phenomenon. This condition directly impact to the packaging industry that supports them. The packaging industry are expected to grow from 101,232 million units in 2016 to 130,325 million units in 2021, registering a CAGR of 5.2%.  PT. Mutiara Jaya Prahasta is one of the players in the packaging industry that offered b2b products across Indonesia. Currently, there is an indication that the production process is inefficient. Furthermore, the company is in transition phase. The site are moving from old building to a new one. Because of this condition, implementing some analysis of the production process is necessary in order to know which alternative for the company to make the production process more efficient especially after moving to a new site.  Then the research is conducted through qualitative research by using interview to collect data and information needed. Furthermore, an analysis is implemented by doing in depth observation to the current production layout. Fishbone Diagram will support to seek root causes in the production process. Which comes from people, equipment, and layout. Simulation by Tecnomatix Software is conducted to see the current layout performance, and the result shows that the current layout performance is not efficient. In order to combat the issue, another simulation need to be done to give alternate options for production layout to increase its efficiency. Another solution to combat the problem that comes from people and equipment is by implementation of Total Productive Maintenance (TPM) Approach. Keywords: Operation Management, Fishbone Diagram, Efficiency, TPM, Tecnomatix Software.